Validation study of GRACE risk scores in indigenous and non-indigenous patients hospitalized with acute coronary syndrome. Issue 1 (December 2015) - Bradshaw, Pamela; Katzenellenbogen, Judith; Sanfilippo, Frank; Hobbs, Michael; Thompson, Peter; Thompson, Sandra
Abstract Background Although cardiovascular disease is the major cause of premature death among Indigenous peoples in several advanced economies, no acute coronary syndrome (ACS) risk models have been validated in Indigenous populations. We tested the validity and calibration of three Global Registry of Acute Coronary Events (GRACE) scores among Aboriginal and non-Aboriginal Australians. Methods GRACE scores were calculated at admission or discharge using clinical data, with all-cause deaths obtained from data linkage. Scores for GRACE models were validated for; 1) in-hospital death, 2) death within 6 months from admission or 3) death within 6 months of discharge (this also for 1 and 5-years mortality). Results Aboriginal patient were younger (62 % aged <55 years versus 15 % non-Aboriginal) and their median GRACE scores lower than non-Aboriginal patients, as was crude mortality at 6 months from admission (6 % vs 10 %) and at 1 and 5 years. After age stratification, risk scores for Aboriginal patients were equivalent or higher, especially among those aged <55 years. There was a trend to more deaths after discharge among Aboriginal patients in each age group, suggesting an age-related under-estimation of risk. The c-statistics for the three GRACE models within both groups were between 0.75 and 0.79. Conclusions We demonstrated for the first time that while the discriminatory capacity of GRACE risk scores among Indigenous Australians is good, the models may need re-calibrating to improve risk stratification in this and other Indigenous groups, where age of onset of coronary disease is much younger than among the original reference population.